2023
DOI: 10.3389/fvets.2023.1150636
|View full text |Cite
|
Sign up to set email alerts
|

Canine circovirus: An emerging or an endemic undiagnosed enteritis virus?

Abstract: Canine Circovirus (CanineCV) belongs to the family Circoviridae. It is an emerging virus described for the first time in 2011; since then, it has been detected in different countries and can be defined as worldwide distribution virus. CanineCV infects domestic and wild canids and is mainly related to hemorrhagic enteritis in canines. However, it has been identified in fecal samples from apparently healthy animals, where in most cases it is found in coinfection with other viral agents such as the canine parvovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…However, CanineCV has been also reported as a single agent even when evaluating the presence of other viral and bacterial pathogens ( 3 , 21 ). We highlight the role of CanineCV as a relevant agent in the study of the canine enteric disease, as has been recently discussed ( 6 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, CanineCV has been also reported as a single agent even when evaluating the presence of other viral and bacterial pathogens ( 3 , 21 ). We highlight the role of CanineCV as a relevant agent in the study of the canine enteric disease, as has been recently discussed ( 6 ).…”
Section: Discussionmentioning
confidence: 91%
“…CanineCV is defined as a worldwide distribution agent since its circulation has been reported on 4 out of 5 continents ( 6 ). The phylogenetic analyses of the reported strains have allowed the sequences to be classified into different clades, whose grouping depends mainly on the geographical location where each sequence was found ( 6 ). CanineCV infects wild and domestic canids, and the infection is associated with clinical pictures of acute gastroenteritis, hemorrhagic diarrhea, signs of vasculitis, lymphadenitis, thrombocytopenia, neutropenia and lymphopenia, which is related to immunosuppressive activity due to damage of the lymphoid tissue, which has been described in circovirus infection in poultry and pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The canine circovirus (CanineCV, species Circovirus canine ) is the sole member of the genus containing viruses currently known to infect canines. CanineCV was first identified in 2012 in serum and tissue samples of North American dogs (Kapoor et al, 2012; Li et al, 2013), and subsequent epidemiological investigations have confirmed its global presence in dogs (Gomez-Betancur et al, 2023). In these studies, clinical signs indicative of gastroenteritis, respiratory disease, and hematological and immune disorders have been found associated with CanineCV infection in domestic dogs.…”
Section: Introductionmentioning
confidence: 99%
“…CanineCV is associated with respiratory diseases and diarrhea in dogs ( Li et al, 2013 ; Decaro et al, 2014 ; Hsu et al, 2016 ; Anderson et al, 2017 ; Cruz et al, 2020 ; Dankaona et al, 2022 ), and CanineCV may also cause immunosuppression due to coinfection with other pathogens, leading to aggravation of clinical symptoms ( Dowgier et al, 2017 ; Kotsias et al, 2019 ). As CanineCV could not effectively replicate on cells, its viral isolation and cultivation in vitro have been unsuccessful ( Gomez-Betancur et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…CanineCV was first identified among dogs in the United States in 2012 ( Kapoor et al, 2012 ). Subsequently, it was reported among dogs in Europe, Asia, and South America ( Gomez-Betancur et al, 2023 ). Hence, the natural host of CanineCV is dog.…”
Section: Introductionmentioning
confidence: 99%